Bone mineral density, vertebral fractures and body mass index in postmenopausal women with abdominal aortic calcification. (7th May 2013) - Simon, Siao-pin; Fodor, Daniela; Muntean, Laura; Poanta, Laura; Cristea, Paulina; Rednic, Simona
Abstract: Background : Evidence suggest that there are connections between osteoporosis and cardiovascular diseases. Objectives : The aim of the study was to analyze the relationship between radiological measurements of abdominal aorta calcifications (AAC) and bone mineral density (BMD) in postmenopausal women. Methods : In this cross-sectional study were included 125 postmenopausal women 50–84 years of age. BMD of the spine and hip was measured by dual energy X-ray absorptiometry (DXA). AAC were assessed by lateral radiographs of lumbar spine (L1–L4), using the antero-posterior severity score (0–24). Vertebral fractures were evaluated from T4 to L4 using Genant's semiquantitative method. Results : Forty-one (32.8%) patients had osteoporosis and 61 (48.8%) had AAC with a mean score of 3.1. Postmenopausal women with AAC were older and had significantly lower femoral neck and trochanteric BMD than subjects without AAC (all p  < 0.01). There were no significant differences in the frequency of fractures between subjects with AAC and those without AAC ( p  > 0.05). In univariate analysis, age, height, weight, femoral and trochanter BMD were significantly associated with the severity of AAC score. In multiple regression analysis, femoral neck BMD, but not lumbar spine, trochanter BMD or age, was an independent predictor of AAC. Conclusions : Reduced femoral neck BMD is negatively associated with the presence of AAC in postmenopausal women. The association between BMD and AAC seems to be age-independent, which suggests a common pathogenesis for bone loss and vascular calcifications.